The Political Defence of the Commons: The Case of Community Networks - Félix Tréguer; Melanie Dulong de Rosnay (tripleC: Communication, Capitalism & Critique)
This article reflects on experiences of political advocacy which have been led by Community Networks activists in Germany, France and Spain to support the sustainability of bottom-up initiatives aiming at building community-owned telecom infrastructures, or “telecommons”. While pointing to the diversity of action repertoires used by various Community Networks across Europe, the article points to the potential of these instances of political advocacy to democratise both telecommunications and policy-making in the telecom sector, an area that is prone to both eviction of small actors and regulatory capture by special economic interests. It also suggests that their repertoires offer a set of reproducible tactics available to very small actors without dedicated advocacy staff or budget. Speaking to the inventiveness of grassroots initiatives, the article concludes by analysing the potential and pitfalls of political advocacy for small-scale social movements working for the political defence of the commons, and communities which are under risk of enclosure and capitalist co-optation.